Enzyme-catalyzed kinetic resolution of racemic 1-octen-3-ol and field evaluation of its enantiomeric isomers as attractants of sandflies - Tchouassi, David P.; Jacob, Juliah W.; Cheseto, Xavier; Chepkemoi, Lydia S.; Hassaballa, Iman B.; Torto, Baldwyn (Frontiers in Tropical Diseases, 2024)
Phlebotomine sand flies are medically important as vectors of the protozoan parasites that cause leishmaniasis and other bacterial and viral pathogens. Previous work demonstrated that both sexes of certain species of sandflies are attracted to 1-octen-3-ol (octenol). Since 1-octen-3-ol exists as two enantiomeric isomers ─ ((R)-(-)- (R-form) and (S)-(+)- (S-form), we tested the hypothesis that the two enantiomeric forms and racemic mixture (R/S) attracted different sand fly species. We carried out field trials in a leishmaniasis endemic foci in Baringo County, Kenya. In a randomized design, trap captures of sandflies in CDC light traps baited with the R-, S- and racemic (R/S) forms of 1-octen-3-ol in hexane varied with the form and dose of the compound. Interestingly, of the captured species, only Phlebotomus martini, the vector of the parasite causing visceral leishmaniasis, exhibited a dose-dependent response to octenol; captures of both sexes of the species being generally 1.7-fold higher with the R- than S-form. There was no significant effect of treatment on captures of Sergentomyia species (S. schwetzi, S. antennata, S, clydei). Our findings have implications for surveillance of sandfly populations as part of leishmaniasis epidemiologic investigation.